Phylogeography of the Sino-Himalayan fern Lepisorus clathratus on "the roof of the world". - Li Wang (PLoS ONE, 2011)
The Qinghai-Tibetan Plateau (QTP) and its southern and southeastern mountain ranges, Himalaya-Hengduan Mountains (HHM), are one of the most extensive habitats for alpine plants in the world. How ferns occurring in QTP and HHM changed their distribution ranges in response to Quaternary climatic oscillations remains almost unknown.We employed sequences of two chloroplast DNA regions, rps4-trnS and trnL-trnF, to reconstruct phylogeography of the Sino-Himalayan fern Lepisorus clathratus, occurring mainly in the QTP and HHM. Individuals of this species have either dehiscent or indehiscent sporangia with the latter evolved from the plesiomorphic dehiscent forms. Based on a range-wide sampling, we detected 27 cpDNA haplotypes that were divided into five groups by network analyses. Populations in the Hengduan Mountains possess the highest genetic diversity, while a single haplogroup is detected across the north-central region. A distinct phylogeographical subdivision was detected between the Hengduan Mountains and north-central region by AMOVA analysis. The haplogroup distribution pattern, coalescence and AMOVA analysis suggest that a long term survival area (refugia) of the species was located in the Hengduan Mountains during glaciations, with probable range expansions into north-central regions during interglacial periods. Populations with indehiscent sporangium can carry private haplotypes and are inclined to maintain genetic homogeneity. One group with indehiscent sporangia most likely survived in situ on the QTP during glaciations.This study for the first time sheds light on the response of alpine ferns in the QTP and HHM to the Quaternary climatic oscillations.